Implementasi Pengembangan Kemampuan Mengenal Huruf Selama Masa Belajar di Rumah Pada Anak - Hikmatul Husna (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2021)
This study describes the implementation of language learning in children aged 4-5 years in TK ABA JOGOKARYAN while studying at home. The assessed research was to describe the implementation of letter recognition in children aged 4-5 years at TK ABA Jogokaryan. This research is a qualitative approach and descriptive research type. The subjects of this study were the principal, class A teachers, parents of class A students, and grade A children. The object of this study was the implementation of letter recognition in children aged 4-5 years at TK ABA JOGOKARYAN in class A2 while studying at home. The data collection techniques used were interviews and documentation. The data analysis technique uses the theory of Miles and Huberman, namely data collection, data condensation, data presentation, and concluding. The validity of the research data was re-tested using source triangulation and method triangulation. The results of this study indicate: 1) Planning begins with making daily lesson plans, then sent to parents via Whatsapp group or give to parents directly when they come to school. 2) The implementation of letter recognition is played by parents by accompanying and documenting the learning activity process. 3) Evaluation is carried out through documentation reported by parents on the Whatsapp group. 4) Supporting factors include guidance from parents in letter recognition while children are studying at home, online media, which is used as a communication tool for teachers and parents, and special programs on television that help children's learning while at home. At the same time, the inhibiting factors are some families who do not make it a habit knowing letters, parents' busyness, mood swings, and a lack of enthusiasm for learning.